Excess mortality and undertreatment in elderly lung cancer patients: treatment nihilism in the modern era?. Issue 2 (24th May 2021) - Pham, Jonathan; Conron, Matthew; Wright, Gavin; Mitchell, Paul; Ball, David; Philip, Jennifer; Brand, Margaret; Zalcberg, John; Stirling, Rob G.
Treatment of elderly patients with lung cancer is significantly hindered by concerns about treatment tolerability, toxicity and limited clinical trial data in the elderly; potentially giving rise to treatment nihilism amongst clinicians. This study aims to describe survival in elderly patients with lung cancer and explore potential causes for excess mortality. Patients diagnosed with lung cancer in the Victorian Lung Cancer Registry between 2011–2018 were analysed (n=3481). Patients were age-categorised and compared using Cox-regression modelling to determine mortality risk, after adjusting for confounding. Probability of being offered cancer treatments was also determined, further stratified by disease stage. The eldest patients (≥80 years old) had significantly shorter median survival compared with younger age groups (<60 years: 2.0 years; 60–69 years: 1.5 years; 70–79 years: 1.6 years; ≥80 years: 1.0 years; p<0.001). Amongst those diagnosed with stage 1 or 2 lung cancer, there was no significant difference in adjusted-mortality between age groups. However, in those diagnosed with stage 3 or 4 disease, the eldest patients had an increased adjusted-mortality risk of 28% compared with patients younger than 60 years old (p=0.005), associated with markedly reduced probability of cancer treatment, after controlling for sex, performance status, comorbidities and histology type (OR 0.24, compared with <60 years old strata; p<0.001). Compared to younger patients, older patients with advanced-stage lung cancer have a disproportionately higher risk of mortality and lower likelihood of receiving cancer treatments, even when performance status and comorbidity are equivalent. These healthcare inequities could be indicative of widespread treatment nihilism towards elderly patients. Treatment strongly determines lung cancer survival, yet nihilism may threaten treatment provision and survival outcomes. Older patients in this cohort had reduced multidisciplinary presentation, less treatment (OR 0.24) and 28% increased mortality risk. https://bit.ly/2ZGotj0